The notion of epitaph in epigraphy and linguistics - Prystay, Nataliya (Видавництво Національного університету «Львівська політехніка», 2009)
Epitaph as a specific discourse type is being studied. Typology of epigraphic inscriptions and classification of epitaphs are being suggested.
Keywords: epitaph; discourse; epigraphy; linguistics